Event management : putting theory into practice : a South African approach - Smit, Laricia (Johannesburg: Masterskill, 2017)
This book focuses on the practical of knowledge for event professionals. The author's industry-related experience, expertise, and a passion for event management guide learners through the entire process, from initial concept to evaluating the strategy after the event.
Bibliography (1-3 pages)
Adult